Maternal Employment in Norway A parity-specific analysis of the return to full-time and part-time work after birth - Marit Rønsen (Statistics Norway, Research Department, 1995)
This paper analyzes the (re)entry of Norwegian mothers into full-time and part-time employment following the first and second birth. Based on theories of job search and human capital depreciation and appreciation a semi-parametric hazard model is estimated, expressing the entry rate as a function of a woman's full wage (the market wage plus the present value of reductions in future earnings due to a career break) and her reservation wage. As predicted, a higher market wage and higher accumulated employment experience before birth are found to speed up the return to work, but the positive effect of employment experience declines with time since birth. The most powerful predictor of after-birth employment is the length of prior home-time periods. Having stayed at home a long time before birth strongly inhibits the return to both full-time and part-time work, and the effect becomes stronger the longer the time since birth. This is in line with the notion that women tend to be either persistent workers or persistent non-workers, as is found in several U.S. studies. New to this study is the evidence of persistency also in full-time and part-time work, as previous full-timers are much more likely to return to full-time and previous part-timers are much more likely to return to part-time work. All in all, there is no evidence that part-time workers have a looser attachment to the labour market than full-time workers.
Keywords: C41; J13; J22; J24; J31; 330; Maternal employment; full-time; part-time; human capital; child-birth; career interruptions; hazard model